Application of Linier Regression Method in Analysis of Farm Business Credit on The Welfare of Farmers in Kedung Lengkong Village, Dlangu Sub-District, Mojokerto District - Heri Susanto; Ramon Syahrial; Adi Budiwan (UNIPA PRESS, 2023)
The role of the agricultural sector can be optimized if it is supported by an integrated sustainable system and capital support. In this study the problems to be discussed are 1) Capital is a problem faced by farmers, 2) Many farmers are able to increase crop yields if they have sufficient capital, 3) Without sufficient capital, farmers will not be able to increase the productivity of their crops. To overcome the problem of lack of capital, farmers borrow money from both formal and informal financial institutions, the purpose of this study is to determine the effect of the efficiency of agricultural credit distribution on the welfare of farmers in the agricultural sector. Agricultural credit plays a very important role in agricultural development: if production increases, farmers' income will also increase. In the research applying quantitative methods where the number of samples is 100 people. With a population of 187 people are farmers in Kedung Lengkong Village, Dlangu District, Mojokerto Regency. In the research the analysis applied is simple regression in order to determine the effect of credit performance on the welfare of farmers. The results of hypothesis testing that credit has a positive influence on happiness is worth the regression coefficient of 0.291. Farmers are helped by credit to buy fertilizers, seeds and others according to agribusiness needs so as to increase profits, as a source of welfare.